Probing the limits of categorization : the bystander in Holocaust history - Morina, Christina 1976- (Studies on war and Genocide, 2018)
"Of the three categories that Raul Hilberg developed in his analysis of the Holocaust--perpetrators, victims, and bystanders--it is the last that is the broadest and most difficult to pinpoint. Described by Hilberg as those who were "once a part of this history," bystanders present unique challenges for those seeking to understand the decisions, attitudes, and self-understanding of historical actors who were neither obviously the instigators nor the targets of Nazi crimes. Combining historiographical, conceptual, and empirical perspectives on the bystander, the case studies in this book provide powerful insights into the complex social processes that accompany state-sponsored genocidal violence"--